Biochemical Characterization of the Pharmacological Effects of Yagari in Experimentally Induced Benign Prostatic Hyperplasia - Agatemor, Uzuazokaro Mark-Maria; Nwodo, Okwesili Fred Chiligue (Planta Medica International Open, 2022)
Benign prostatic hyperplasia is a progressive pathologic condition common in ageing men, constituting a health burden. Benign prostatic hyperplasia is characterized by the proliferation of prostatic tissues, prostate enlargement, and lower urinary tract symptoms. The use of herbal medicine in the management and treatment of benign prostatic hyperplasia has shown some promise. The efficacy and potency of some polyherbal extracts have been scientifically proven in the management and treatment of diseases, while many others are yet to be investigated. The aim of this study was to determine the effect of the herbal mixture Yagari on experimentally induced benign prostatic hyperplasia in rats and to identify its pharmacologically active agents. The effect of the herbal mixture on experimentally induced benign prostatic hyperplasia in rats was determined using 36 male Wistar rats grouped randomly into 6 groups of 6 rats each. The test rats were treated subcutaneously using a combination of dihydrotestosterone and estradiol valerate in a 10:1 ratio for 28 days according to the standard method. The test rats were thereafter treated with the herbal mixture for 21 days. Prostate-specific antigen, inflammatory cytokines, assay of prostate function hormonal and prostate function enzyme activities, and kidney function test were evaluated in the blood samples collected by ocular puncture applying standard methods. Prostates were harvested and examined for histopathological changes. Biological activity-guided fractionation of Yagari in a silica gel column was carried out and using phospholipase A2 activity as a biomarker. The identity of the bioactive compounds was determined using mass spectroscopy and nuclear magnetic resonance. The herbal mixture showed a positive effect on prostatic hyperplasia by decreasing urinary obstruction through the inhibition of 5-alpha reductase, anti-inflammatory activity, and decreased level of sex hormones. Characterization by spectral studies revealed apigenin (4´,5,7-trihydroxyflavone, molecular weight).
Keywords: Nauclea latifolia; Erythrophleum suaveolens; Rubiaceae; Fabaceae; Yagari; prostatic hyperplasia; prostatitis